Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/978-3-319-21993-6_3
|View full text |Cite
|
Sign up to set email alerts
|

Hygiene and Sanitation in Biogas Plants

Abstract: The increasing number of agricultural biogas plants and higher amounts of digestate spread on agricultural land arouse a considerable interest in the hygiene situation of digested products. This chapter reviews the current knowledge on sanitation during anaerobic digestion and the hygienic status of digestate concerning a multitude of pathogens potentially compromising the health of humans, animals and plants. Physical, chemical and biological parameters influencing the efficiency of sanitation in anaerobic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 121 publications
0
19
0
Order By: Relevance
“…It had been reported that about 6.5 million metric ton (dry weight) of sewage sludge were generated annually, in which waterborne pathogens may be concentrated substantially (Shen et al, 2015). As such, biosolid disposal sites might act as the sources of pathogens, leading to a potential risk of uncontrollable spread into surface water, ground water and soils (Fröschle et al, 2015a(Fröschle et al, , 2015b. Without proper control, sludge-associated pathogens could continue to grow, causing potential threats to the human health.…”
Section: Introductionmentioning
confidence: 99%
“…It had been reported that about 6.5 million metric ton (dry weight) of sewage sludge were generated annually, in which waterborne pathogens may be concentrated substantially (Shen et al, 2015). As such, biosolid disposal sites might act as the sources of pathogens, leading to a potential risk of uncontrollable spread into surface water, ground water and soils (Fröschle et al, 2015a(Fröschle et al, , 2015b. Without proper control, sludge-associated pathogens could continue to grow, causing potential threats to the human health.…”
Section: Introductionmentioning
confidence: 99%
“…The presence and behaviour of diverse human, animal and plant pathogens was addressed in a series of studies as recently reviewed (Franke-Whittle and Insam 2013; Avery et al 2014;Fr€ oschle et al 2015;Insam et al 2015). The presence and behaviour of diverse human, animal and plant pathogens was addressed in a series of studies as recently reviewed (Franke-Whittle and Insam 2013; Avery et al 2014;Fr€ oschle et al 2015;Insam et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The digestate could be used as manure as an alternative to raw feces, limiting the spread of pathogens [5].…”
Section: Methodsmentioning
confidence: 99%